(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
The inventory and assessment of species diversity in the mono-generic family Begoniaceae C. A. Agardh of Bangladesh were made through long term field investigations, collections, identification, survey and examination of preserved herbarium specimens and review of relevant taxonomic and floristic literature. The family is recognized to be represented in the flora of Bangladesh by 19 species under the genus Begonia L. Of these, 11 species were known to be previously recorded from the area of Bangladesh, hence additional 8 species of the present account are being reported here for the first time as new records from Bangladesh, these are: Begonia grandis Dryand. ssp. holostylla Irmsch. , B. heracleifolia Cham. and Schltdl. Cult., B. maculata Raddi Cult. B. modestiflora Kurz, B. muliensis T. T. Yu. Cult., B. scintillans Dunn, B. surculigera Kurz and B. thomsonii A. DC. An enumeration of these 19 species is prepared, and each species is cited with detailed taxonomic data. All species of the Begonia L. are herbaceous in nature and possess potential economic values, viz. 11 (52%) medicinal, 5 (24%) ornamental, 3 (14%) beverage, 1 (5%) food and 1 (5%) poisonous. Determination of status of occurrence showed that 2 (10.53%) species are common, 5 (26.32%) cultivated, 9 (47.36%) threatened and 3 (15.79%) possibly extinct in Bangladesh. Field photographs and hand drawings of recorded taxa are provided. J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(1): 35-46